A Review on User Perception of Desktop and Mobile Service Website Using Webqual and User Experience Approach - Rizqiyatul Khoiriyah; Apol Pribadi Subriadi (IPTEK Journal of Proceedings Series, 2015)
As the online media dissemination, website has the advantages that it can be accessed freely, without limits, wherever, whoever, and whenever. However, the advantages of the website is sometimes not in line with its simplicity. So it becomes important that the organization can make an assessment of the quality of the website that they are used, whether its website has fulfilled what is perceived by the user. This paper reviews studies user perception of desktop and mobile service website used qualitative methods adapted to WebQual and User Experience approach. The expected outcome of this research is knowing the user's perception of the services and information available on the website along with the possibility of desktop and mobile gap arising from differences in the two services.